Associations of fat‐soluble micronutrients and redox biomarkers with frailty status in the FRAILOMIC initiative. Issue 6 (21st August 2019) - Kochlik, Bastian; Stuetz, Wolfgang; Pérès, Karine; Pilleron, Sophie; Féart, Catherine; García García, Francisco José; Bandinelli, Stefania; Gomez‐Cabrero, David; Rodriguez‐Mañas, Leocadio; Grune, Tilman; Weber, Daniela
Abstract: Background: A poor fat‐soluble micronutrient (FMN) and a high oxidative stress status are associated with frailty. Our aim was to determine the cross‐sectional association of FMNs and oxidative stress biomarkers [protein carbonyls (PrCarb) and 3‐nitrotyrosine] with the frailty status in participants older than 65 years. Methods: Plasma levels of vitamins A (retinol), D3, E (α‐tocopherol and γ‐tocopherol) and carotenoids (α‐carotene and β‐carotene, lycopene, lutein/zeaxanthin, and β‐cryptoxanthin), PrCarb, and 3‐nitrotyrosine were measured in 1450 individuals of the FRAILOMIC initiative. Participants were classified into robust, pre‐frail, and frail using Fried's frailty criteria. Associations between biomarkers and frailty status were assessed by general linear and logistic regression models, both adjusted for cohort, season of blood sampling, gender, age, height, weight, and smoking. Results: Robust participants had significantly higher vitamin D3 and lutein/zeaxanthin concentrations than pre‐frail and frail subjects; had significantly higher γ‐tocopherol, α‐carotene, β‐carotene, lycopene, and β‐cryptoxanthin concentrations than frail subjects, and had significantly lower PrCarb concentrations than frail participants in multivariate linear models. Frail subjects were more likely to be in the lowest than in the highest tertile for vitamin D3 (adjusted odds ratio: 2.15; 95% confidence interval: 1.42–3.26), α‐tocopherol (2.12; 1.39–3.24), α‐carotene (1.69; 1.00–2.88), β‐carotene (1.84; 1.13–2.99), lycopene (1.94; 1.24–3.05), lutein/zeaxanthin (3.60; 2.34–5.53), and β‐cryptoxanthin (3.02; 1.95–4.69) and were more likely to be in the highest than in the lowest tertile for PrCarb (2.86; 1.82–4.49) than robust subjects in multivariate regression models. Conclusions: Our study indicates that both low FMN and high PrCarb concentrations are associated with pre‐frailty and frailty.